1983
DOI: 10.3133/ofr83328
|View full text |Cite
|
Sign up to set email alerts
|

Effect of soil structure interaction on seismograms

Abstract: This paper discusses the effect of soil structure interaction on seismoqrams. In particular, seismograms of the 1979 Imperial Valley earthquake, taken from two instruments located close together, are discussed. One of these instruments is down hole and the other one is housed inside the recorder structure. It is shown that soil structure interaction theory accounts well for the differences in the measured vertical accelerations but not so well for the horizontal accelerations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2009
2009
2010
2010

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…Vol. 166, 2009 Effect of Velocity Inversions on H/V 579 The interaction between soil and structure (i.e., the place where the seismic instrument is set, which partly resembles the effect of taking a recording on a stiff artificial layer) was studied by CROUSE et al (1984), CROUSE and HUSMAND (1989) and BYCROFT (1978). Soil-structure coupling acts in two opposite ways: 1) Tall pedestals have the effect of amplifying the horizontal components of motion while 2) short and large (with respect to horizontal wave length) foundations, as those studied in this work, decrease the horizontal components.…”
Section: Theoretical Modellingmentioning
confidence: 99%
“…Vol. 166, 2009 Effect of Velocity Inversions on H/V 579 The interaction between soil and structure (i.e., the place where the seismic instrument is set, which partly resembles the effect of taking a recording on a stiff artificial layer) was studied by CROUSE et al (1984), CROUSE and HUSMAND (1989) and BYCROFT (1978). Soil-structure coupling acts in two opposite ways: 1) Tall pedestals have the effect of amplifying the horizontal components of motion while 2) short and large (with respect to horizontal wave length) foundations, as those studied in this work, decrease the horizontal components.…”
Section: Theoretical Modellingmentioning
confidence: 99%
“…In 1941 Washburn found that the geophone-ground coupling system seriously interfered the amplitude and phase of the seismic records. Later many scholars such as Miller and Pursey (1954), Bycroft (1957Bycroft ( , 1978, Lamar (1970), Hoover and O'Brien (1980) have studied the influence of the coupling system when the geophone was well-coupled with the surface soil based on the wave theory. But their theoretical models neglected the impact of the geophone spike [6∼11] .…”
Section: Introductionmentioning
confidence: 99%